Prevalence of diabetes and impaired glucose metabolism in younger 'at risk' UK adults: insights from the STAND programme of research. Issue 6 (12th April 2013) - Wilmot, E. G.; Edwardson, C. L.; Biddle, S. J. H.; Gorely, T.; Henson, J.; Khunti, K.; Nimmo, M. A.; Yates, T.; Davies, M. J.
Abstract Aims Rising rates of obesity have led to an increasing prevalence of Type 2 diabetes mellitus in young people. Uncertainty exists over the utility of screening younger adults for Type 2 diabetes, as existing data sets have focused on mature (> 40 years) cohorts. The aim of this study was to determine the prevalence of impaired glucose metabolism in higher risk younger adults. Methods Overweight (with an additional risk factor) or obese adults (18–40 years) were recruited for the Sedentary Time And Diabetes (STAND) randomized controlled trial. Measures included an oral glucose tolerance test, HbA1c, biochemical and anthropometric data. Results One hundred and ninety‐three individuals (68% female; median age 33.8 years; median BMI 33.9 kg/m2) were recruited. Forty‐three per cent had a first‐degree family history of Type 2 diabetes. Previously undiagnosed Type 2 diabetes was present in 4.7% (n = 9). Of participants, 18.1% (n = 35) had impaired glucose metabolism: 4.7% (n = 9) HbA1c ≥ 48 mmol/mol (6.5%); 9.3% (n = 18) HbA1c 42–46 mmol/mol (6.0–6.4%); 3.1% (n = 6) Type 2 diabetes on oral glucose tolerance test; 6.2% (n = 12) isolated impaired glucose tolerance; 2.1% (n = 4) isolated impaired fasting glucose; 1% (n = 2) both impaired fasting glucose and impaired glucose tolerance. Of participants, 58.5% (n = 113) had dyslipidaemia, 28.0% (n = 54) had hypertension, 31.1% (n = 60) were vitamin D deficient and 7.3% (n = 14) had abnormal liver function. Conclusions This study identified a high prevalence of Type 2 diabetes and impaired glucose regulation in overweight and obese younger adults. These findings require confirmation in a larger, representative, population.